Management of varicella zoster virus exposure and infection (chickenpox) in pregnancy and neonates - Fernandopulle, Rohini; Ranganathan, Shilani Sri (Sri Lanka College of Paediatricians, 2001)
Varicella-zoster virus infections in pregnancy can cause severe adverse effects in the mother, fetus and neonate, which vary with the period of gestation. For the mother the adverse effects are greatest in the second half of pregnancy whereas for the fetus it is greatest in the first and second trimester.
Keywords: Varicella-zoster virus infections in pregnancy; adverse effects